2021
DOI: 10.1155/2021/5847153
|View full text |Cite
|
Sign up to set email alerts
|

Polygoni Multiflori Radix Preparat Delays Skin Aging by Inducing Mitophagy

Abstract: Background. As the skin is the largest organ of the human body, it is aging inevitably and produces cosmetic and psychological problems, and even disease. Therefore, the molecular mechanisms related to the prevention of skin aging need to be further explored. Methods. Aging models were constructed by D-galactose. Mice were administrated with polygoni multiflori radix preparat (PMRP), PMRP and 3-methyladenine, or PMRP and rapamycin intragastrically. The apparent and viscera index of aged rats was measured. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Dysregulated mitophagy is commonly seen in cardiovascular pathologies, including cardiac hypertrophy, heart failure and dilated cardiomyopathy [ 12 , 13 ]. Downregulation of mitophagy has been reported to contribute to the organ aging process [ [14] , [15] , [16] ]. Notably, defective mitophagy is commonly observed in aging cardiomyocytes, which leads to the accumulation of defective mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated mitophagy is commonly seen in cardiovascular pathologies, including cardiac hypertrophy, heart failure and dilated cardiomyopathy [ 12 , 13 ]. Downregulation of mitophagy has been reported to contribute to the organ aging process [ [14] , [15] , [16] ]. Notably, defective mitophagy is commonly observed in aging cardiomyocytes, which leads to the accumulation of defective mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Moldenke (Polygonaceae), is a popular traditional Chinese medicine that has been used for hair darkening, prolonging life, and mitigating several dysfunctions ( Tang et al, 2017 ). Modern pharmacological research and clinical practices have shown that RPM has several bioactive properties, including antioxidant ( Liu X. et al, 2021 ; Wang et al, 2008 ), antiaging ( Cheung et al, 2014 ; Fan et al, 2021 ), and antitumor activities ( Ma et al, 2012 ; Hou et al, 2013 ; Way et al, 2014 ; Lin et al, 2017 ; Xing et al, 2019 ), and it helps in regulating immunity ( Chen et al, 2012 ), lowering blood lipids ( Yao et al, 2013 ; Chang et al, 2016 ; Xie et al, 2012 ), and promoting neuroprotection ( Sun et al, 2011 ; Yang X.-P. et al, 2014 ; Ruan et al, 2021 ). However, an increasing number of recently published studies have demonstrated the adverse effects of RPM.…”
Section: Introductionmentioning
confidence: 99%
“…e reproductive system is susceptible to the influence of toxicants [41], so research on reproductive toxicity is indispensable. Viscera index is an objective, practical, and sensitive indicator in toxicology, which can directly reflect the comprehensive toxicity of viscera after medication and is an essential clue to the target organ of toxicant action; e decrease or increase of viscera index can reflect the atrophy or congestion of viscera [42].…”
Section: Discussionmentioning
confidence: 99%